PENGARUH PELATIHAN PERTOLONGAN PERTAMA PADA SINKOP TERHADAP PENGETAHUAN DAN PRAKTEK PADA SISWA PMR - Mokhtar Jamil; Merisdawati Merisdawati (Jurnal Surya, 2026)
Introduction: Syncope is a temporary loss of consciousness caused by a transient reduction in cerebral blood flow and is commonly experienced by adolescents in school settings. Syncope may result in injuries due to falls and requires prompt and appropriate first aid management. Youth Red Cross (Palang Merah Remaja/PMR) members play an important role in providing first aid at school; however, their knowledge and practical skills in managing syncope vary considerably. This study aimed to analyze the effect of syncope first aid training on the knowledge and practice of PMR students. Methods: This study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 25 PMR students from SMK Muhammadiyah 7 Gondanglegi selected through total sampling. The intervention was syncope first aid training delivered through lectures, demonstrations, and practical simulations. Knowledge was assessed using a structured questionnaire, while practice was evaluated using an observation checklist based on the Standard Operating Procedure (SOP) for syncope first aid. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of α < 0.05. Results: Prior to the training, most participants demonstrated a moderate level of knowledge (44%) and a passing level of practice (56%). Following the training, the proportion of participants with good knowledge increased from 20% to 44%, while the proportion achieving a passing practice score increased from 56% to 72%. The Wilcoxon test revealed a significant effect of the training on both knowledge (p = 0.000) and practice (p = 0.004). Conclusion: Syncope first aid training was effective in improving the knowledge and practical skills of PMR students in managing syncope incidents. Educational programs combined with practical simulations are recommended to enhance students’ preparedness and competence in providing first aid in school environments. Keywords: syncope, first aid, training, knowledge, practice, Youth Red Cross (PMR).